2006
DOI: 10.1093/ndt/gfl620
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of percutaneous ethanol injection therapy (PEIT) is related to the number of parathyroid glands in haemodialysis patients with secondary hyperparathyroidism

Abstract: Superior results in efficacy rate, remission period and risk of relapse are obtained when PEIT is restricted to patients with one hyperplastic gland > or =0.5 cm(3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
1
36
0
9
Order By: Relevance
“…When overlooked during parathyroidectomy, the ectopic gland may cause persistent or recurrent hyperparathyroidism [107]. For patients who refuse or are not candidates for surgery, direct injection of ethanol [108] or active vitamin D into the parathyroid [109] may be considered, although long-term control of SHPT would be obtained only in patients with one enlarged gland [110].…”
Section: Treatment Of Shptmentioning
confidence: 99%
“…When overlooked during parathyroidectomy, the ectopic gland may cause persistent or recurrent hyperparathyroidism [107]. For patients who refuse or are not candidates for surgery, direct injection of ethanol [108] or active vitamin D into the parathyroid [109] may be considered, although long-term control of SHPT would be obtained only in patients with one enlarged gland [110].…”
Section: Treatment Of Shptmentioning
confidence: 99%
“…But one study has demonstrated that PEIT is effective in the treatment of single parathyroid adenomas [20]. Koiwa et al [11] also had similar results, reporting that for patients with only one hyperplastic gland (>0.5 cm 3 ) PEIT had superior efficacy rates.…”
Section: Discussionmentioning
confidence: 93%
“…A number of patients fail to respond to medical therapy and may have to undergo parathyroidectomy (PTX) [4]. Percutaneous ethanol injection therapy (PEIT) was first reported by Solbiati et al [5] as an alternative to PTX in patients with high surgical risk and its effectiveness had already been documented by other authors [6,7,8,9,10,11]. However, a high recurrence rate is a frequent problem because of a patient’s lack of cooperation, ectopic parathyroid mass and, mainly, incomplete treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Guidelines of the Japanese Society for Parathyroid Intervention, PEIT is recommended in patients with one large parathyroid gland [105]. Koiwa et al analyzed to what extent the number of hyperplastic gland influence the PEIT effect, finding a better rate of success in terms of efficacy and remission period in those patients with one hyperplastic parathyroid gland [106]. Ethanol injection also represents a reasonable option in cases of persistence of SHPT after PTx.…”
Section: Percutaneous Direct Injection Therapymentioning
confidence: 99%